1999
DOI: 10.1002/1529-0131(199907)42:7<1473::aid-anr22>3.0.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

Detection ofBorrelia burgdorferi sensu stricto by reverse line blot in the joints of Dutch patients with Lyme arthritis

Abstract: The relationship between different species of B. burgdorferi sensu lato and arthritis can be studied using direct analysis of extracted DNA from joint samples. This method can be used to study the association between particular clinical manifestations of Lyme disease and different species of B. burgdorferi sensu lato.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
16
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 45 publications
1
16
0
Order By: Relevance
“…Generally, B. afzelii is a rodent specialist, B. garinii and B. valaisiana are associated with birds, and B. lusitaniae is associated with lizards (7,16,22,32). The clinical manifestations of Lyme borreliosis in humans differ depending on the Borrelia species; B. garinii is associated with neurological diseases, while B. burgdorferi and B. afzelii are more likely to cause arthritis and cutaneous symptoms, respectively (2,4,5,36).…”
mentioning
confidence: 99%
“…Generally, B. afzelii is a rodent specialist, B. garinii and B. valaisiana are associated with birds, and B. lusitaniae is associated with lizards (7,16,22,32). The clinical manifestations of Lyme borreliosis in humans differ depending on the Borrelia species; B. garinii is associated with neurological diseases, while B. burgdorferi and B. afzelii are more likely to cause arthritis and cutaneous symptoms, respectively (2,4,5,36).…”
mentioning
confidence: 99%
“…Different studies have presented indirect evidence for the association of B. garinii with predominantly neurological symptoms (5), while infections by B. burgdorferi sensu stricto and B. afzelii tend to lead to arthritic symptoms (29) and cutaneous manifestations (3), respectively. New rapid and sensitive methods are therefore required for differentiating the three pathogenic Borrelia species to test the strengths of these associations.…”
mentioning
confidence: 99%
“…Based on ospA sequence variation analysis, it has previously been reported that in Europe B. burgdorferi sensu lato strains causing Lyme arthritis are very heterogeneous with no prevalence of certain genospecies (6,18). In contrast, more recently published studies demonstrated a preponderance of B. burgdorferi sensu stricto DNA in joint samples from Lyme arthritis patients (7,17).…”
mentioning
confidence: 99%